'Responsibility to Prosecute' in an age of global governmentality: The International Criminal Court. (March 2016) - Turan, Gozde
This paper critically examines the discursive power of the International Criminal Court (ICC), which was established in 2002 with unprecedented jurisdiction in terms of both crimes being prosecuted and territorial scope. What evokes a critical engagement is not only the criminalization of certain acts in international law, but also the evolution of a permanent international criminal court with forms of power enabling the sanctioning, prosecution and punishment of these acts. Analysing how current international criminal law developed and is being shaped brings to the surface particular power structures embedded in legal texts and practices. By subjecting the discourse of the ICC to a Foucauldian analysis and arguing for the utility of Foucault's concepts in analysing contemporary international criminal legal discourse, the paper contributes to our understanding of novel techniques and procedures of contemporary global governmentality, and how the 'international community' is constituted as both a subject and an object within this recent power modality.